By Practitioners, For Practitioners: Informing and Empowering Practice Through Practitioner Research - Cordelia Zinskie; Dan Rea (National Youth Advocacy and Resilience Journal, 2016)
The National Youth-At-Risk Journal was developed to provide meaningful information and resources for professionals who work with youth placed at risk. In order to further this goal, we are calling on practitioners to communicate directly with their colleagues via the journal. We are especially interested in publishing practitioner reports on effective programs, strategies, or interventions that improve both the practice and well-being of youth. The editors provide an overview of practitioner research, describe three approaches to practitioner research, outline the process for conducting practitioner research, and emphasize the role of practitioner-researchers as agents of change. Resources are provided to assist practitioners in conducting research and in reporting their experiences and outcomes.